2011
DOI: 10.1371/journal.pone.0016976
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Efficacy and Safety of Intermittent Preventive Treatment of Malaria in Children (IPTc)

Abstract: BackgroundIntermittent preventive treatment of malaria in children less than five years of age (IPTc) has been investigated as a measure to control the burden of malaria in the Sahel and sub-Sahelian areas of Africa where malaria transmission is markedly seasonal.Methods and FindingsIPTc studies were identified using a systematic literature search. Meta-analysis was used to assess the protective efficacy of IPTc against clinical episodes of falciparum malaria. The impact of IPTc on all-cause mortality, hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
132
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 29 publications
13
132
2
Order By: Relevance
“…9,29 Combination therapies for IPTc such as amodiaquine plus sulfadoxine-pyrimethamine or artesunate plus sulfadoxine-pyrimethamine have been effective in areas of seasonal malaria transmission. 9,29,30 Emerging antimicrobial drug resistance has spread through malariaendemic areas and has made treatment difficult. 31 We did not measure resistance to azithromycin in Plasmodium because we were unable to perform cultures at our field site and biochemical assays for this have not been adequately described.…”
Section: Discussionmentioning
confidence: 99%
“…9,29 Combination therapies for IPTc such as amodiaquine plus sulfadoxine-pyrimethamine or artesunate plus sulfadoxine-pyrimethamine have been effective in areas of seasonal malaria transmission. 9,29,30 Emerging antimicrobial drug resistance has spread through malariaendemic areas and has made treatment difficult. 31 We did not measure resistance to azithromycin in Plasmodium because we were unable to perform cultures at our field site and biochemical assays for this have not been adequately described.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 12 clinical IPTc studies in sub-Saharan Africa including Senegal using SP, but always combined with another drug (amodiaquine AQ), have demonstrated impressive protective efficacies against clinical malaria episodes ranging from 31% to 93% (overall protective efficacy of 82% (95% CI = 75-87%). 9 Furthermore, it was shown that IPTc protected against all-cause mortality by 57% (95% CI = 24-76%). 9 Thus, IPTc is highly effective and furthermore, well tolerated.…”
Section: Introductionmentioning
confidence: 98%
“…9 Furthermore, it was shown that IPTc protected against all-cause mortality by 57% (95% CI = 24-76%). 9 Thus, IPTc is highly effective and furthermore, well tolerated. 10 -12 Therefore, WHO recommended IPTc, 13 now named Seasonal Malaria Chemoprevention (SMC) and the intervention will most likely be adopted large scale in areas where malaria transmission is seasonal.…”
Section: Introductionmentioning
confidence: 98%
“…Resistance is occurring as a consequence of several factors, including poor treatment practices, inadequate patient adherence to prescribed antimalarial regimens, widespread availability of artemisininbased monotherapies and substandard forms of the drug [9,10]. In recent years, parasite resistance to artemisinins -the key compounds in artemisinin combination therapy (ACTs) -has been detected in four countries of the Greater Mekong subregion: Cambodia, Myanmar, Thailand and Vietnam in agreement with the prediction of the World Health Organization (WHO) 2010 [6].…”
Section: Introductionmentioning
confidence: 99%